2021
DOI: 10.1002/aic.17511
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on breakup of a single bubble in a stirred tank: Effect of gas density and liquid properties

Abstract: Bubble breakup plays an important role in gas–liquid flows, but detailed studies are still scarce. In this work, the breakup behavior of a single bubble in a stirred tank was experimentally studied with a high‐speed camera, focusing on the effect of gas density, liquid properties, agitation speed, and mother bubble size. The bubble breakup time, breakup probability, breakup rate, and daughter bubble size distribution were determined. The internal‐flow phenomenon that the gas flowed from the smaller part to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 66 publications
4
14
0
Order By: Relevance
“…This is due to two opposite effects of pressure on the gas holdup of small bubbles. On one hand, the elevated pressure reduces the internal flow in deformed bubbles, which enhances the bubble breakup and then increases the gas holdup of small bubbles 57 . Moreover, this enhancing effect intensifies with an increase in bubble size 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to two opposite effects of pressure on the gas holdup of small bubbles. On one hand, the elevated pressure reduces the internal flow in deformed bubbles, which enhances the bubble breakup and then increases the gas holdup of small bubbles 57 . Moreover, this enhancing effect intensifies with an increase in bubble size 17 .…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the elevated pressure reduces the internal flow in deformed bubbles, which enhances the bubble breakup and then increases the gas holdup of small bubbles. 57 Moreover, this enhancing effect intensifies with an increase in bubble size. 17 In ethanol-water system, the probability of bubble coalescence is reduced due to Marangoni stress, leading to a notable increase of smaller bubbles, thus a low rate of bubble breakup.…”
Section: Gas Holdupmentioning
confidence: 99%
“…To verify these models, a large number of experimental data on fluid particle breakage are required. Several studies have reported experiments of breakage frequency and DSD for bubble and drop, respectively 12,22–42 (summarized in Tables S3.1 and S3.2). Some experiments showed that the breakage frequency monotonically increased with increasing fluid particle size 12,23–30 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported experiments of breakage frequency and DSD for bubble and drop, respectively 12,22–42 (summarized in Tables S3.1 and S3.2). Some experiments showed that the breakage frequency monotonically increased with increasing fluid particle size 12,23–30 . However, the non‐monotonic trend was also observed.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical agitation is the most common method to enhance mixing/ mass transfer in industries [1,2]. It refers to forcing fluids flow in a vessel by mechanical means, or to the random distribution of two or more separate phases between one another, e.g., by mixing two miscible liquids, dissolving a solid in a liquid, and dispersing a gas in a liquid to form fine bubbles [3,4]. These processes are commonly used in chemical engineering processes including hydrogenation, polymerization, crystallization, fermentation, wastewater treatment, etc.…”
Section: Introductionmentioning
confidence: 99%